Pengembangan Penghijauan pada Kawasan Permukiman di Bumi Tamalanrea Permai Makassar - Yohana Todingrara; Ananto Yudono; Marly Valenti Patandianan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2014)
The increasing of the population growth is proportional to the demand of built up land. This happens to the settlement where the construction of various facilities continues to increase, so that the area of land for green open space increasingly limited. The lack of the green open space is caused by the land conversion to the built up area. In addition, it has a lot of construction that do not pay attention to the Building Coverage Ratio (BCR) and the Green Grounds Coefficients so that the availability of the green open space in the house yard is very limited. The reduced and even the loss of the green open space area which should be available impact on various problems incidence, such as air pollution, floods, and the rising of the temperature of town. This happens in Bumi Tamalanrea Permai settlement where the availability of the green open space decreased along with the increasing of built up land growth. This research aims to knowing the characteristic and functions of the green open space in Bumi Tamalanrea Permai settlement that for each type is varies and influenced by its widely and locations, then to determine the ratio of green area per resident in which it is not reached the standard that is 20 meter square per resident. The analysis is conducted by qualitative and quantitative approaches. From the results of analysis conducted, there are several problems relate to the green open space in Bumi Tamalanrea permai settlement, so that the green development direction is a solution in order that availability of the green open space is still exist even though with the limited land.